PENGARUH INKLUSI KEUANGAN DAN INVESTASI TERHADAP PENYERAPAN TENAGA KERJA DAN TINGKAT KEMISKINAN KABUPATEN/KOTA DI PROVINSI BALI - Made Suyana Utama, Ni Kadek Ayu Junitadewi (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Poverty is one of the fundamental problems in any country. Some of the factors that cause decline in poverty levels are financial inclusion, investment and labor absorption. The purpose of this stuy was to 1) analyze the effects of financial inclusion and investment on labor absorption, 2) analyze the effects of financial inclusion, investment and labor absorption on poverty levels, 3) analyze the effects of financial inclusion and investment on poverty levels through labor absortion. Technical analysis uses path analysis techniques with 72 observation points. Data collection through BPS and Bank Indonesia. Path analysis was used. The results of the analysis show that financial inclusion have a positive and significant direct influence on labor absorption. Investment have a positive but not significant direct influence on labor absorption. Financial inclusion and investment has a negative and significant direct influence on poverty levels and labor absorption has a negative but not significant direct influence on poverty levels. Financial inclusion and investment do not have an indirect effect on the level of poverty through labor absorption.